Network based location tracking using MAC address of smart devices - Chowdhury, Md. Abu Hena; Chowdhury, Rakib Hasan; Hossain, Shoaib; Sakib, Sadman Md (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.